PENGARUH METODE PEMBELAJARAN DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN MATEMATIKA SISWA KELAS V SD SEKECAMATAN CIPAYUNG JAKARTA TIMUR - Septi Fitri Meilana (Jurnal Akrab Juara, 2019)
This study aims to determine the effect of teaching methods and learning motivation toward math skills. This research was conducted at SDN 03 Pagi Cipayung, Cipayung subdistrict of East Jakarta on class V first semester. using cluster random sampling. Data were collected through tests and analyzed using Analysis of Variance (ANOVA) with a two-way design treatments by level 2 x 2. The ruesults showed that: (1) the ability of the students are taught mathematics teaching methods higher than students taught using expository method, (2) there is an interaction effect between teaching methods and learning motivation toward math skills, (3) for students who have high learning motivation , mathematical skills of students who are taught using methods of learning while playing higher than students taught using expository method, (4) for students who have low learning motivation, students are taught using methods of learning while playing lower than students taught using methods espositori.